2021
DOI: 10.1002/qua.26650
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric oxidation of 4‐(2‐methoxyethyl) phenol initiated by OH radical in the presence of O2 and NOx: A mechanistic and kinetic study

Abstract: 4-(2-Methoxyethyl) phenol (MEP) plays an important role in the formation of secondary organic aerosols (SOA). The gas-phase mechanism and kinetics of MEP with OH reaction are studied by the density functional theory (DFT). The initial reactions of MEP with OH radical produce two different channels: OH addition and H abstraction. Subsequent reaction schemes of the main intermediates are investigated by using M06-2X/6-311++G(3df,2p)//M06-2X/6-311+G(d,p) level. Ketene, diketones and nitrophenol compounds are demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…However, the reaction rate constants involving water vapor could be calculated by TST. Previous studies have shown that the kinetic calculations for gas-phase reactions could provide better results [ 40 , 49 , 54 ]. And gas-phase rate constants could be changed to aqueous-phase ones.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the reaction rate constants involving water vapor could be calculated by TST. Previous studies have shown that the kinetic calculations for gas-phase reactions could provide better results [ 40 , 49 , 54 ]. And gas-phase rate constants could be changed to aqueous-phase ones.…”
Section: Resultsmentioning
confidence: 99%
“…The tunneling correction factor κ ( T ) was calculated using the Wigner model: where lm( V ≠ ) is the transition state’s imaginary frequency. Some studies have used the KiSThelP program to calculate rate constants, with good results [ 48 , 49 , 50 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional Transition State Theory (TST) was used to calculate the rate constants implemented by KiSThelP program [34] that has obtained accurate results for contaminants with free radicals reactions [35][36][37][38][39]. The calculation formula is employed in KiSThelP:…”
Section: Kinetic Calculationmentioning
confidence: 99%
“…Fan et al reported negative activation energies during the OH initiated oxidation processes of phenol [13]. Yao et al used M062X theory to study the oxidation processes of 4‐(2‐methoxyethyl) phenol initiated by OH radical [14]. However, the underlying reaction mechanisms of organic micropollutants oxidized by OH radical are still not totally understood.…”
Section: Introductionmentioning
confidence: 99%